2021
DOI: 10.1101/2021.12.24.21268174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence in Southern France of a new SARS-CoV-2 variant of probably Cameroonian origin harbouring both substitutions N501Y and E484K in the spike protein

Abstract: SARS-CoV-2 variants have become a major virological, epidemiological and clinical concern, particularly with regard to the risk of escape from vaccine-induced immunity. Here we describe the emergence of a new variant. For twelve SARS-CoV-positive patients living in the same geographical area of southeastern France, qPCR testing that screen for variant-associated mutations showed an atypical combination. The index case returned from a travel in Cameroon. The genomes were obtained by next-generation sequencing w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…One such scenario, based on positive reinforcement interactions of two pools of population, is described in this work as a possible mechanism of accumulation of positive mutations leading to emergence of variants similar to Omicron. An indirect support for a mechanism of this type is provided by another variant with a large number of mutations reported recently [9]. Further studies in the communities where these variants originated may provide essential inputs for validation or rejection of the hypothesis of accelerated variant production discussed in this work.…”
Section: Discussionmentioning
confidence: 75%
“…One such scenario, based on positive reinforcement interactions of two pools of population, is described in this work as a possible mechanism of accumulation of positive mutations leading to emergence of variants similar to Omicron. An indirect support for a mechanism of this type is provided by another variant with a large number of mutations reported recently [9]. Further studies in the communities where these variants originated may provide essential inputs for validation or rejection of the hypothesis of accelerated variant production discussed in this work.…”
Section: Discussionmentioning
confidence: 75%
“…F490S was first identified in the Lambda variant and again in certain Delta subvariant (Novazzi et al, 2022). Most recently, F490R has been found in some Omicron subvariant (Colson et al, 2021), suggesting a continued immune pressure towards the identified VH1-69 "HCDR2" epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Some changes between both lineages are that the spike genes differ by seven mutations, and more 25 nucleotide substitutions and 33 nucleotide deletions have been detected. It is necessary to assess whether commercially available vaccines are able neutralize a new variant or whether the new genomic variant induces viral escape [27].…”
Section: B16402mentioning
confidence: 99%